Who are our clients: consumer segmentation through explorative data mining. (1st January 2012) - Viktor, Herna L.; Peña, Isis; Paquet, Eric
The apparel industry aims to produce comfortable and aesthetically pleasing garments that fit populations well. However, repeated studies of apparel customers' levels of satisfaction indicate that their needs are often not being met. In order to produce better fitting clothes, it is crucial to understand the body profiles of typical consumers. Exploring the demographic profiles of correctly identified customer segments holds obvious benefit for production, marketing and ensuring return on investments. To this end, we explore a database, containing anthropometric measurements, demographic profiles and 3-D body scans, of samples of the North American, Italian and Dutch populations. Through the use of objective interestingness measures-based feature selection and feature extraction, we accurately discover the relevant subsets of body measurements that require special care when designing clothes. Furthermore, we apply association analysis to the demographic data, in order to target customers and thus potentially defining new market opportunities.